Speech Accommodation Without Priming: The Case of Pitch. Issue 4 (18th May 2016) - Gijssels, Tom; Casasanto, Laura Staum; Jasmin, Kyle; Hagoort, Peter; Casasanto, Daniel
Abstract : People often accommodate to each other's speech by aligning their linguistic production with their partner's. According to an influential theory, the Interactive Alignment Model, alignment is the result of priming. When people perceive an utterance, the corresponding linguistic representations are primed and become easier to produce. Here we tested this theory by investigating whether pitch (F0) alignment shows two characteristic signatures of priming: dose dependence and persistence. In a virtual reality experiment, we manipulated the pitch of a virtual interlocutor's speech to find out (1) whether participants accommodated to the agent's F0, (2) whether the amount of accommodation increased with increasing exposure to the agent's speech, and (3) whether changes to participants' F0 persisted beyond the conversation. Participants accommodated to the virtual interlocutor, but accommodation did not increase in strength over the conversation and disappeared immediately after the conversation ended. Results argue against a priming-based account of F0 accommodation and indicate that an alternative mechanism is needed to explain alignment along continuous dimensions of language such as speech rate and pitch.